New religious movements : challenge and response - Wilson, Bryan R.; Cresswell, Jamie (London ; New York : Routledge, 1999)
Focusing on five countries (Italy, Brazil, Germany, Britain and the United States), New Religious Movements offers a comprehensive and wide-ranging study of the phenomena and impact of new religions.
Chapter Introduction / BRYAN WILSON -- part Summary of Chapter 1 -- chapter 1 New Religious Movements: Their incidence and significance / EILEEN BARKER -- part Summary of Chapter 2 -- chapter 2 The Easternisation of the West / COLIN CAMPBELL -- part Summary of Chapter 3 -- chapter 3 Prosperity and the New Age Movement: The efficacy of spiritual economics / PAUL HEELAS -- part Summary of Chapter 4 -- chapter 4 New Religious Movements: The legal dimension / ANTHONY BRADNEY -- part Summary of Chapter 5 -- chapter 5 The mass media and New Religious Movements / JAMES A. BECKFORD -- part Summary of Chapter 6 -- chapter 6 New Religious Movements and mental health / LAWRENCE LILLISTON -- part Summary of Chapter 7 -- chapter 7 Women in New Religious Movements / ELIZABETH PUTTICK -- part Summary of Chapter 8 -- chapter 8 New Religious Movements and the Churches / COLIN SLEE -- part Summary of Chapter 9 -- chapter 9 Damanhur: a magical community in Italy / MASSIMO INTROVIGNE -- part Summary of Chapter 10 -- chapter 10 Japanese New Religious Movements in Brazil: from ethnic to 'universal' religions / PETER B. CLARKE -- part Summary of Chapter 11 -- chapter 11 Anti-cultists in the United States: An historical perspective / J . GORDON MELTON -- part Summary of Chapter 12 -- chapter 12 The response to New Religious Movements in East Germany after reunification / FRANK USARSKI -- part Summary of Chapter 13 -- chapter 13 Britain's anti-cult movement / GEORGE D. CHRYSSIDES.
Includes bibliographical references and index.
Print version record.
Keywords: Religions; Cults; Sects; Religions; Cultes; Sectes; RELIGION -- Comparative Religion; Cults; Religions; Sects; Sekte; Religiöse Bewegung; Aufsatzsammlung; Godsdienstige bewegingen; Electronic books